Менеджмент трансакційних витрат підприємств - Комбарова, К. С.; Горбаль, Н. І.; Kombarova, K. S.; Horbal, N. I. (Видавництво Львівської політехніки, 2022)
Проаналізовано сутність та роль трансакційних витрат, показано, що їх частка на підприємствах є значною. Виявлено тенденції до зростання таких витрат на вітчизняних підприємствах і вказано причини високого їх рівня. Подано класифікацію трансакційних витрат підприємств. Виділено ключові фактори, які ускладнюють контроль та мінімізацію трансакційних витрат. Наведено приклади виникнення прихованих трансакційних витрат. Описано взаємозв’язок між такими витратами й ланцюгом створення цінності підприємств і показано, що не всі групи трансакційних витрат пов’язані зі стадіями створення продукції. Наведено приклади впливу цих витрат на виробничий процес. Показано, що застосування пропонованих заходів забезпечить зниження трансакційних витрат і позитивно вплине на рівень витрат підприємств загалом й сприятиме підвищенню ефективності їхньої діяльності.

The essence and role of transaction costs are analyzed; it is shown that their share in enterprises is significant. Transaction costs, in particular, are defined as costs in the field of exchange related to acts of sale, transfer of property rights, emphasizing that they are not directly related to the production process of enterprises, but to organizational issues of their activities. Modern business conditions lead to an increase of transaction costs, associated with an expansion of the range of counterparties, a continuous increase in information flows, specific costs depending on ownership factors, etc. Trends in growth of such costs at domestic enterprises were identified and reasons for their high level were given. Classification of transaction costs of enterprises is presented. Key factors that complicate the control and minimization of transaction costs are highlighted. Examples of hidden transaction costs are given. Relationship between such costs and the value creation chain of enterprises is described, and it is shown that not all groups of transaction costs are related to the stages of product creation. Examples of impact of these costs on a production process are presented. In general, increase in the scale of enterprises' activities due to the addition of related industries to their composition can lead to a decrease in transaction costs. On the other hand, due to the increase in a size of the enterprise and the complexity of its structure, the costs of its general management are increasing. The optimal size of the enterprise can be reached when the savings from the reduction of transaction costs associated with the growth of the enterprise will become equal to the additional costs of managing it. It is shown that application of the proposed measures will ensure reduction of transaction costs and will positively affect the level of expenses of enterprises in general and contribute to the growth of the efficiency of their activities.
Management of transaction costs of enterprises
Keywords: витрати; трансакційні витрати; управління витратами; приховані витрати; скорочення витрат; підприємство; costs; transaction costs; cost management; hidden costs; cost reduction; enterprise; 338.583; 336.717.063